Multidimensional repair of jujube pectic oligosaccharides on bone marrow hematopoietic failure - Chen, Hongxi; Wang, BiYing; Li, XianZhen (Frontiers in Nutrition, 2026)
Jujube, a valued resource in traditional practices for both medicine and diet, has been historically recognized for its blood-nourishing properties. Nevertheless, the potential of its active constituent, Jujube Pectic Oligosaccharides (JOL), to ameliorate myelosuppressive anemia remains poorly understood. This research was therefore designed to elucidate the therapeutic efficacy and underlying mechanism of JOL using a murine model of cyclophosphamide-induced myelosuppression. Our findings demonstrate that JOL administration effectively restored multi-lineage peripheral blood cell counts, improved the structural integrity of the spleen and bone marrow, and modulated key hematopoietic factors. These critical factors comprised erythropoietin (EPO), Flt3 ligand (Flt3-L), thrombopoietin (TPO), and granulocyte colony-stimulating factor (G-CSF). Collectively, the results indicate that Jujube oligosaccharides could mitigate myelosuppressive anemia via synergistic multi-target effects, possibly by rehabilitating the damaged hematopoietic microenvironment and normalizing the cytokine network equilibrium. This investigation offers foundational experimental support for the development of JOL as a promising therapeutic candidate for myelosuppression.